Are You Threatening Me? Identity Threat, Resistance to Persuasion, and Boomerang Effects in Environmental Communication. Issue 2 (17th February 2022) - Ma, Yanni; Hmielowski, Jay D.
ABSTRACT : In today's increasingly polarized political environment, people are becoming resistant to persuasive messages, which creates challenges for those communicating about environmental issues to the public. Scholars have noted that opinion-challenging information could either be ineffective or lead to boomerang effects. As a result, research has started to examine the underlying mechanism of why messages are ineffective, with a specific emphasis on boomerang effects. We conducted three experiments to examine the role of environmental identity threat as a trigger of defense mechanisms and boomerang effects. In general, our study finds that identity threat from a message leads to increased psychological reactance, counter-arguing, and anxiety. There is also evidence that boomerang effects flow through identity threat and both counter-arguing and anxiety. Our results cast light upon designing persuasive messages to encourage individuals to engage in environmental behaviors without antagonizing them.